The issue of the use of exotic wood in external building partitions - Sudol, Ewa; Sulik, Paweł (Budownictwo i Architektura / Civil and Architectural Engineering, 2013)
Exotic wood species are more often used in windows, doors, facades and shutters. A multitude of species and unique properties make its use is difficult. The use of exotic wood in outside partitions, exposed to the different climatic conditions, should be preceded by verification of its properties, sometimes specific (glueability, susceptibility to impregnation or finish paint coatings), which determining the reliability and durability of the final product.